PENGARUH RELIGIUSITAS, PRODUK, PROMOSI, DAN LOKASI TERHADAP MINAT MENABUNG MASYARAKAT PADA LEMBAGA KEUANGAN MIKRO SYARIAH (STUDI PADA KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH BAITUL MAAL WA TAMWIL USAHA GABUNGAN TERPADU SIDOGIRI KANTOR CABANG KRAMAT - Auliya, Yusma Rosmatul; Puspita (Journal of Accounting, Management and Islamic Economics, 2025)
This study aims to discuss the influences that influence the interest in society saving at Sharia Microfinance Institutions, study on KSPPS BMT UGT Sidogiri Branch Office in Kramat Jati. The independent variables obtained from the preliminary survey results are Religiosity, Product, Promotion, and Location. While the dependent variable obtained is the customer interest in saving. Methods of data analysis using multiple regression. The population is savings customers, with a sample of 100 respondents. The sampling technique used purposive sampling. By using a quantitative descriptive approach. The results of this study indicate that Religiosity has a significant positive effect on customer interest in saving, Product has a significant positive effect on customer interest in saving, Promotion has a significant positive effect on customer interest in saving, and Location has a significant positive effect on customer interest in saving.